Gammagrafía de glándulas submaxilares - Fredchteyn de Eskenazi, Silvia (1984)
Eighty nine patients with early unilateral Bell's palsy had a sub-mandibularsalivary gland scan. Tecnetium-99m was used.  Alterations in the uptake of the radioisotope in the salivary gland of the paralised side were studied, when the lesion was up to the chordis thimpany outcome.  Correlation between this study and others methods to evaluate the submandibular function were made (E. Stapedius Reflex test). The results shows the high value of this study in the prognostic evaluation of the Bell's Palsy evolution.